ANALISIS KELAYAKAN FINANSIAL DAN EKONOMI USAHATANI BERINGIN DOLAR - Emmy Hamidah (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2017)
This research aims to analyze: (1) financial feasibility of cultivating tanamam Banyan Village Tulungwanar dollars in the Sub Shoots lamongan. (2) the rate of increase in sensitivity to the cost of production, a decrease in production and a decrease in output prices in the village of tulung wanar sub shoots lamongan. The location of the research conducted in the village of Tulungwanar Sub-district Shoots Lamongan. The data used are the primary data and secondary data. Data analysis is the analysis of quantitative and qualitative descriptive analysis. Quantitative analysis of financial feasibility analyse (B/C Ratio, NPV, IRR, and PP) and analysis of rate sensitivity by using the DF 15%. Qualitative descriptive analysis is used to find out the feasibility of aspects of cultivation, technical aspects, and aspects of the market. Data collection was carried out in February 2016. The results showed that (1) the intensive Cultivation of crops in the villages of Tulungwanar dollar Banyan Sub Shoots Lamongan deserves to be organised with the Gross value of the B/C Ratio amounted to 4.7; NET B/C Ratio 9.94; NPV of Rp 278,880,609; IRR of 35%. (2) the possibility of cost of production goes up 10%, 25% production decrease, or a decrease in output prices 10% of farming the cultivation of crops in the State of the dollar is still to be viable and profitable. (3) the aspect of the cultivation of climate and rainfall according to plant Banyan dollars. The technical aspect of the majority of farmers are still using simple technology, a lot of technology that is available has not been applied. Aspects of the market even though in terms of sales is not just like any other crop cultivation yet still decent and still very promising.